Pengembangan LKPD PjBL Terintegrasi Kearifan Lokal Pembuatan Garam Madura untuk Kelas IV SDN Saronggi 1 - Tarika, Siti; Pritasari, Ade Cyntia (Jurnal Riset Madrasah Ibtidaiyah (JURMIA), 2024)
The purpose of this development research is to (1) develop teaching materials for LKPD PjBL integrated with local wisdom of Madura salt making for grade IV SDN Saronggi 1 which is valid based on expert validation. (2) develop teaching materials for LKPD PjBL integrated with local wisdom of making Madura salt for grade IV SDN Saronggi 1 which is effective based on student learning test results. (3) developing teaching materials for LKPD integrated with local wisdom of Madura salt making for grade IV SDN Saronggi 1 which is interesting based on teacher response questionnaire and student response. This research is a development research that refers to the ADDIE model (analyze, design, development, implementation, evaluation). Based on the results of the study, the percentage of validity of LKPD PjBL teaching materials integrated with local wisdom of Madura salt making in terms of material validation is 91.7%, teaching material validation is 94.1%, learning design validation is 95.5%, each of which is in the "very valid" category. The effectiveness of LKPD PjBL teaching materials integrated with the local wisdom of making Madura salt in terms of classical learning outcomes amounted to 100% with complete criteria. Attractiveness in terms of teacher responses obtained a percentage of 98.4% and student responses obtained a value of 94.8%, each of which was in the very attractive category. Based on the results obtained, the PjBL LKPD integrated with the local wisdom of making Madura salt for class IV SDN Saronggi 1 is valid, effective, and interesting.